Tirzepatide (Zepbound) - CDA-AMC (Canadian Journal of Health Technologies, 2026)
Canada’s Drug Agency (CDA-AMC) recommends that Zepbound be reimbursed by public drug plans for once-weekly administration for chronic weight management, including weight loss and weight maintenance, as an adjunct to a reduced-calorie diet and increased physical activity, in adults with a body mass index (BMI) of greater than or equal to 27 kg/m2 and prediabetes, if certain conditions are met. The Canadian Drug Expert Committee (CDEC) concluded that Zepbound does not demonstrate acceptable clinical value compared with appropriate comparators (reduced-calorie diet and increased physical activity; semaglutide) for the full Health Canada indicated population (adults with a BMI of greater than or equal to 30 kg/m2 [obesity], or BMI of 27 kg/m2 to less than 30 kg/m2 [overweight] in the presence of at least 1 weight-related comorbid condition). However, CDEC concluded that Zepbound demonstrates acceptable clinical value compared with appropriate comparators (reduced-calorie diet and increased physical activity) in the subpopulation of adults with a BMI of greater than or equal to 27 kg/m2 and prediabetes. This determination was enough for CDEC to recommend that Zepbound be reimbursed. Given that Zepbound is expected to be an additive treatment to reduced-calorie diet and increased physical activity in this subpopulation, acceptable clinical value refers to added value versus reduced-calorie diet and increased physical activity alone. Three phase III randomized controlled trials (SURMOUNT-1, SURMOUNT-2, and SURMOUNT-4) showed that Zepbound, when combined with diet and physical activity, resulted in clinically meaningful reductions in body weight and increased the likelihood of achieving 5% or greater weight loss compared with placebo over 52 to 72 weeks in adults with overweight or obesity. In the prediabetes subgroup of the SURMOUNT-1 trial, Zepbound also reduced progression to type 2 diabetes mellitus (T2DM) through 176 weeks. While improvements in quality of life and functioning were observed, their clinical importance remains uncertain. No major safety concerns were identified, although long-term harms are unknown. Evidence on the impact of Zepbound on long-term clinical outcomes (e.g., cardiovascular events, mortality) and its comparative efficacy versus relevant comparators is lacking. Overall, the evidence is most supportive of a clinically meaningful benefit in patients with overweight or obesity and prediabetes since this subpopulation demonstrated sustained weight loss over the longest period of follow-up and a reduced risk of developing T2DM. Zepbound should only be covered for adults who have a BMI of 27 kg/m2 or greater and prediabetes, and at least 1 self-reported unsuccessful dietary attempt at weight loss. Zepbound should only be reimbursed for chronic weight management if the patient is following a reduced-calorie diet and engaging in increased physical activity and if the cost of Zepbound is reduced. For continuation of reimbursement after the first year of treatment, at least a 5% reduction in total body weight from baseline must be documented. Thereafter, patients should be reassessed each year. Zepbound should not be reimbursed for use in combination with other glucagon-like peptide-1 (GLP-1) receptor agonists (RAs).